How do perceptions of relative poverty affect women's empowerment? Evidence from Papua New Guinea - Kosec, Katrina; Mo, Cecilia Hyunjung; Schmidt, Emily; Song, Jie (International Food Policy Research Institute, 2019)
How do perceptions of one’s relative economic status affect gender attitudes, including support for women’s economic participation and involvement in decision-making? We conducted a 2018 survey experiment with female and male adults in approximately 1,000 households in Papua New Guinea. Employing an established survey treatment to subtly alter respondents’ perception of their relative economic well-being, we find that increased feelings of relative poverty make both men and women significantly more likely to support girls’ schooling and women’s paid employment, suggesting that relative economic insecurity can prompt support for women’s economic participation. However, increased feelings of relative poverty may trigger greater intra-household tension. While increased perceptions of relative poverty cause women to want more household decision-making authority, men’s attitudes toward women’s roles in decision-making are unchanged. Results underscore the complicated nature of gender attitudes, and how support for women’s economic participation may rise without simultaneous increases in women’s agency in decision-making.